2019
DOI: 10.37897/rjp.2019.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and complications of acute gastroenteritis in hospitalized children

Abstract: Etiology and complications of acutE gastroEntEritis in hospitalizEd childrEn student nardin Elias, assist. prof. daniela pop, md, phd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Another study from the central region of Romania identified Campylobacter spp. as the primary bacterial enteric pathogen, followed by Salmonella spp., Klebsiella spp., and EPEC; however, this study included children up to 14 years old [22]. Our study identified STEC as the predominant etiological agent, followed closely by EPEC, and by Salmonella spp., Shigella spp., and Yersinia spp.…”
Section: Discussionmentioning
confidence: 77%
“…Another study from the central region of Romania identified Campylobacter spp. as the primary bacterial enteric pathogen, followed by Salmonella spp., Klebsiella spp., and EPEC; however, this study included children up to 14 years old [22]. Our study identified STEC as the predominant etiological agent, followed closely by EPEC, and by Salmonella spp., Shigella spp., and Yersinia spp.…”
Section: Discussionmentioning
confidence: 77%
“…El contagio persona a persona se produce en especial en patógenos que requieren una pequeña cantidad de inoculo para producir infección. 8 Rev Mex Patol Clin Med Lab 2020; 67 (3): 129-141 www.medigraphic.com/patologiaclinica www.medigraphic.org.mx…”
Section: Comorbilidad Asociadaunclassified